218 Development of Pneumatic System for Granular Fertilizer Flow Rate Control - Talha, Zahir.; Tola, E.; F. Kheiralla, A.; Algaadi, K. (University of Khartoum Engineering Journal, 2022)
Variable-rate technology is an essential part of precision farming that can solve the economical and environmental problems associated with traditional farming practices. Utilization of the technology has been limited by the lack of the development of variable-rate applicators. In this study control system equipped with pneumatic circuit was composed of a double acting cylinder, a double solenoid operated valve 5/2, a computer, a microcontroller, a rotary encoder, and other operating parts. The control system performance and discharge characteristics were evaluated. The main results of this study could be summarized as follows: (i) the automatic setting of the target fertilizer application rate could be performed efficiently, (ii) the developed system could be precisely used for granular fertilizer variable rate application, and (iii) the collected observations indicated that the developed system could be significantly used for granular fertilizer variable rate applications with an overall error (from the target rate) in the range of ±6%. This work will be a useful contribution in the area of variable rate technology. Further research work to improve the developed control system and to evaluate its performance under actual field conditions is recommended.